Handbook of Vitamins - Zempleni, Janos (CRC Press, 2014)
Vitamins play essential roles in many processes fundamental to life. Within the last few years, knowledge about vitamins has increased dramatically resulting in improved understanding of human requirements for many vitamins. This new edition of a bestseller presents comprehensive summaries that analyze the chemical, physiological, and nutritional relationships as well as highlight newly identified functions for all recognized vitamins. Maintaining its status as the highest quality reference in the field, the Handbook of Vitamins brings together leading experts in molecular biology, biochemistry, and physiology to incorporate these new discoveries into this updated and revised fifth edition.